2012
DOI: 10.1038/nature11583
|View full text |Cite
|
Sign up to set email alerts
|

Impaired intrinsic immunity to HSV-1 in human iPSC-derived TLR3-deficient CNS cells

Abstract: In the course of primary infection with herpes simplex virus 1 (HSV-1), children with inborn errors of TLR3 immunity are prone to HSV-1 encephalitis (HSE) 1–3. We tested the hypothesis that the pathogenesis of HSE involves non hematopoietic central nervous system (CNS)-resident cells. We derived induced pluripotent stem cells (iPSCs) from the dermal fibroblasts of TLR3- and UNC-93B-deficient patients and from controls. These iPSCs were differentiated into highly purified populations of neural stem cells (NSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
265
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(277 citation statements)
references
References 42 publications
11
265
0
1
Order By: Relevance
“…These findings were supported by subsequent analysis of patients with defects in genes encoding the TLR3 signalling components TRIF, TBK-1 and IRF3 [35][36][37]. An impaired TLR3-inducible type-1 IFN response to HSV-1 in neurons and oligodendrocytes in the central nervous system (CNS) was subsequently linked with this condition [32][33][34][35][36][37]. These findings are also consistent with studies in mouse models of DNA virus infections.…”
Section: Role Of Tlr3 In Host Defencesupporting
confidence: 74%
See 1 more Smart Citation
“…These findings were supported by subsequent analysis of patients with defects in genes encoding the TLR3 signalling components TRIF, TBK-1 and IRF3 [35][36][37]. An impaired TLR3-inducible type-1 IFN response to HSV-1 in neurons and oligodendrocytes in the central nervous system (CNS) was subsequently linked with this condition [32][33][34][35][36][37]. These findings are also consistent with studies in mouse models of DNA virus infections.…”
Section: Role Of Tlr3 In Host Defencesupporting
confidence: 74%
“…Patients with mutations in TLR3 and UNC93B1 are susceptible to HSV-1 encephalitis [32][33][34]. Recognition by TLR3 of intermediate dsRNA produced by HSV-1 during its replicative cycle likely explains this phenomenon [32].…”
Section: Role Of Tlr3 In Host Defencementioning
confidence: 99%
“…TLR3 can recognize viral dsRNA intermediates. With the aid of induced pluripotent stem cell (iPSC) technology, we and our colleagues Lorenz Studer and Luigi Notarangelo demonstrated that the mutations in these patients impaired intrinsic antiviral immunity in neurons and oligodendrocytes, accounting for the brain-tropic nature of HSE (123). The central nervous system-restricted nature of HSE is explained by the TLR3-independence of most other cell types, including leukocytes and keratinocytes, tested for responses to dsRNAs (117,121).…”
Section: Hse: a Genetic Diseasementioning
confidence: 99%
“…7 However, only 10 of the 120 children or young adults with HSE studied by our group to date have been found to carry mutations affecting the TLR3 pathway. Two have autosomal dominant (AD) partial TLR3 deficiency 8 and a third has autosomal recessive (AR) complete TLR3 deficiency.…”
mentioning
confidence: 99%
“…6 TLR3 is expressed on CNS-resident cells that are permissive for HSV-1 infection. 7 High susceptibility to HSV-1 infection in patient-specific induced pluripotent stem cell (iPSC)-derived UNC-93B-and TLR3-deficient neurons and oligodendrocytes has been demonstrated recently.…”
mentioning
confidence: 99%